Perilaku Kehidupan Sosial Ekonomi Masyarakat Pada Kawasan PT Trimega Bangun Persada (TBP) Di Desa Kawasi Kecamatan Obi Kabupaten Halmahera Selatan Provinsi Maluku Utara - Luwudara, Yostinus; Kaunang, Markus .; Londa, Very Y (JURNAL ILMIAH SOCIETY, 2015)
Kawasi village social life before 2005 was very orderly and organized and put together in every social life. However, reality shows there are currently several changes in the value / norm is happening in the community Kawasi. By using a qualitative design of this study attempts to analyze the behavior of social and economic life of society in Region Trimega PT Bangun Persada In the village Obi Kawasi District of South Halmahera in North Maluku province.The results showed that the presence of industry which is managed by the company PT Trimega Bangun Persada (TBP) in the village Kawasi economically very helpful changes in the revenue structure of society, children were able to continue their education to university level as well as health care and transportation has been very available. However, the advances in tandem with behavioral deviation which is characterized by erosion of the value of the customs, mutual cooperation and social norms of society, so that people's lives are more likely to imitate Kawasi modern lifestyle is presented from the outside.Â Keywords: Behavior, Social Economy, Society